2010
DOI: 10.1177/0886109910375210
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Drug Offers of Rural Hawaiian Youths: A Mixed-Methods Analysis

Abstract: This study examined the gender differences in drug-offer situations of Native Hawaiian youths in rural communities. Youths from seven middle or intermediate schools (N 194) on the Big Island of Hawai'i completed a survey that focused on the drug offers they had received. Multivariate and bivariate analyses indicated that the girls received significantly more drug offers than did the boys in the sample and found it more difficult to refuse drugs in such situations. Qualitative data gathered from communities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
3
22
1
Order By: Relevance
“…Although prior research indicated that rural Hawaiian girls are at higher risk for drug offers and report more difficulty in refusing drugs in offer situations (Okamoto, Kulis, et al, 2010), the social context may place rural Hawaiian boys at higher risk for actual drug use based on the present findings. The findings further suggest that the developmental and social context of drug use may be different for Hawaiian boys and girls, similar to research focused on other Native youth populations (e.g., Novins & Mitchell, 1998).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Although prior research indicated that rural Hawaiian girls are at higher risk for drug offers and report more difficulty in refusing drugs in offer situations (Okamoto, Kulis, et al, 2010), the social context may place rural Hawaiian boys at higher risk for actual drug use based on the present findings. The findings further suggest that the developmental and social context of drug use may be different for Hawaiian boys and girls, similar to research focused on other Native youth populations (e.g., Novins & Mitchell, 1998).…”
Section: Discussioncontrasting
confidence: 67%
“…This study contributes to a developing body of pre-prevention research focused on Native Hawaiian youth and drug use (Edwards et al, 2010; Okamoto, Kulis, et al, 2010; Okamoto, Helm, et al 2010). Collectively, this body of research can inform existing evidence-based drug prevention programs through cultural adaptation efforts; however, the process of adapting existing interventions to unique cultural groups can be complex and difficult (Castro, Barrera, & Holleran-Steiker, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research indicated that Hawaiian girls were exposed more frequently to offers to use drugs and/or alcohol, and found it more difficult to refuse these offers, compared to their male counterparts. 46 Amid these strong situational demands to use drugs and alcohol, the present findings suggest that the curriculum may promote positive interpersonal relationships for Hawaiian girls. More specifically, the focus on non-confrontational resistance skills within the curriculum may provide a means by which rural Hawaiian girls can maintain relational harmony while achieving the goal of drug refusal.…”
Section: Discussionmentioning
confidence: 65%
“…Based on the focus group findings, 62 discrete drug-related problem situations were developed, and were quantitatively validated in multiple studies (Okamoto, Helm, Giroux, Edwards, & Kulis, 2010; Okamoto, Kulis, Helm, Edwards, & Giroux, 2010; Okamoto, Kulis, Helm, Edwards, & Giroux, in press). The scripts developed, adapted, and validated in the present study were based on seven of the most frequently experienced and challenging problem situations experienced by rural Hawaiian youth, which have been outlined in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%